Digitalisasi Administrasi Migrasi: Implementasi Teknologi dalam Pengelolaan Imigrasi dan Kependudukan - Daffa Raihan Arya Mas’adi (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
Digitalization of migration administration is a strategic step in increasing the efficiency and transparency of immigration and population management. This research aims to analyze the implementation of digital technology, such as the M-Paspor application, Immigration Management Information System (SIMKIM), and the Sobat Dukcapil platform, as well as the challenges faced in this process. Descriptive qualitative research methods were used by collecting data through literature studies, interviews and digital system observations. The research results show that digitalization has succeeded in speeding up administrative services, increasing the accuracy of biometric verification, and facilitating data integration. However, the main challenges include limited technological infrastructure, gaps in human resource competencies, resistance to change, and security and data privacy risks. The research conclusions emphasize the importance of multi-stakeholder commitment, increased infrastructure capacity, and clear regulations to ensure the sustainability of digital transformation. Digitalization has the potential to optimize public services, as long as it is accompanied by a holistic strategy to overcome technical, social and policy obstacles.